Biomechanical study of patellofemoral joint instability - Senavongse, Wongwit (My University, 2005)
Patellofemoral joint instability is a complex clinical problem. It may be a consequence of pre-existing anatomical abnormality or trauma. The objectives of this study were to use experimental mechanics to measure patellar stability and to quantify the effects of pathological abnormalities on patellar stability in vitro. Eight fresh-frozen cadaver knees were studies. The patellar stability was measured using an Instron material testing machine. A total load of 175N was applied to the quadriceps muscles. Patellar force-displacement was tested at different knee flexion angles as the patella was cyclically displaced 10mm laterally and medially. Three pathological abnormalities were applied; VMO malfunction, flat lateral trochlea, and medial retinacular structure rupturing. For the first time, this study has shown comparative and quantitative influence of pathological abnormalities on patellar stability. It was found that a flat lateral trochlea has greater effect than the medial retinacular rupturing whereas the medial retinacular rupturing has greater effect than VMO malfunction on patellar lateral stability. These results are important for future investigations on the treatment of patellofemoral instability.
Keywords: Biomechanics; Knee joint; Patella; Patellar stability